PENGARUH IMBANGAN PROTEIN DAN ENERGI TERHADAP KECERNAAN NUTRIEN RANSUM DOMBA GARUT BETINA (The Effect of Protein to Energy Ratios on Nutrient Digestibility of Female Garut Sheep’s Diets) - N. Teti; I. Hernaman; B. Ayuningsih; D. Ramdani; Siswoyo Siswoyo (Jurnal Ilmu dan Teknologi Peternakan, 2018)
This research aimed to study the effect of protein and energy on nutrient digestibility of female Garut sheep’s diet. About 20 heads of female Garut sheep with average body weight 15.72 ± 1.33 kg, allocated into 4 different treatment diets of different protein to TDN (energy) ration i.e. R1=11.53%:63.13%; R2=10.78%:70.06%; R3=13.54%:63.18%; and R4=13.67:69.18%. A completely randomized design was used and the collected data was analyzed with Duncan’s test. The results showed that crude protein and fiber digestibilities of R2 and R4 were higher (P<0.05) than that of R1 and R3, whereas nitrogen free extract and extract ether digestibilities did not have any different among all of treatments. It is concluded that protein to energy ratio of 10.78%:70.06% and 13.67%:69.18% gave the higher diet nutrient digestibility than that of other diets.